Effect of Inflammation on Gingival Mesenchymal Stem/Progenitor Cells’ Proliferation and Migration through Microperforated Membranes: An In Vitro Study - M. Al Bahrawy; K. Ghaffar; A. Gamal; K. El-Sayed; V. Iacono (Stem Cells International)
Background. In the field of periodontal guided tissue regeneration, microperforated membranes have recently proved to be very promising periodontal regenerative tissue engineering tools. Regenerative periodontal approaches, employing gingival mesenchymal stem/progenitor cells in combination with these novel membranes, would occur mostly in inflamed microenvironmental conditions intraorally. This in turn entails the investigation into how inflammation would affect the proliferation as well as the migration dynamics of gingival mesenchymal stem/progenitor cells. Materials and Methods. Clones of human gingival mesenchymal stem/progenitor cells (GMSCs) from inflamed gingival tissues were characterized for stem/progenitor cells’ characteristics and compared to clones of healthy human GMSCs (n=3), to be subsequently seeded on perforated collagen-coated poly-tetra-floro-ethylene (PTFE) membranes with a pore size 0.4 and 3 microns and polycarbonic acid membranes of 8 microns pore size in Transwell systems. The population doubling time and the MTT test of both populations were determined. Fetal bovine serum (FBS) was used as a chemoattractant in the culturing systems, and both groups were compared to their negative controls without FBS. Following 24 hours of incubation period, migrating cells were determined on the undersurface of microperforated membranes and the membrane-seeded cells were examined by scanning electron microscopy. Results. GMSCs demonstrated all predefined stem/progenitor cell characteristics. GMSCs from inflamed gingival tissues showed significantly shorter population doubling times. GMSCs of inflamed and healthy tissues did not show significant differences in their migration abilities towards the chemoattractant, with no cellular migration observed in the absence of FBS. GMSCs from healthy gingival tissue migrated significantly better through larger micropores (8 microns). Scanning electron microscopic images proved the migratory activity of the cells through the membrane pores. Conclusions. Inflammation appears to boost the proliferative abilities of GMSCs. In terms of migration through membrane pores, GMSCs from healthy as well as inflamed gingival tissues do not demonstrate a difference in their migration abilities through smaller pore sizes, whereas GMSCs from healthy gingival tissues appear to migrate significantly better through larger micropores.